Activity during rest breaks, fitness level and injuries in professional ballet dancers - Rakovac, M.; Sajkovic, D. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Working days of professional ballet dancers are characterized by long working hours and significant physical demand (Twitchett et al., 2010). Morning classes are followed by rehearsals and evening performances, with usually short breaks in between. Physical fitness is crucial for performance and injury prevention and many dancers undertake supplemental training to improve their fitness level (Dang et al., 2022). Less is known about the effects of rest-break activities. The aim of the study was to evaluate the difference in physical fitness and injury occurrence between dancers based on their activity during rest breaks. METHODS: Participants were members of a professional ballet ensemble (n=40, 26 females; age (mean±SD) 31.3±7.7 y; height 170.2±7.2 cm; body mass 58.5±10.1 kg). Data on rest-break activity (active/inactive) during a working day was collected via questionnaire. Injury incidence and related time loss from dance was monitored during a one-year period. Muscular fitness was tested by curl-up repetition test, back extension, push-ups, plank and Sargent jump test. Aerobic fitness was assessed by Astrand-Rhyming cycle ergometer test. Balance was tested by single-leg 30s balance test and flexibility by sit-and-reach test and bilateral plantar flexion ROM. Dancers were tested in high-demand period of mid-season. The differences in physical fitness and injury-related time loss between the active and inactive group were tested by Student`s t-test. The relationship between rest-break activity and injury occurrence was tested by Chi-square test for independence. RESULTS: Curl-up repetition test was the only test in which active and inactive group differed significantly (47.9±26.3 vs 33.0±16.8 (n; mean±SD), respectively, t=-2.2, p=.035). In all other tests, except Astrand-Rhyming and Sargent tests, there was a trend of better average results in the active group, although without significant difference. Age, supplemental training and ensemble position were accounted for. There was no significant association between rest-break activity and injury occurrence (Pearson Chi-square=0.61, p=.44). Eighteen participants were injured during the monitored period. There was no difference between active and inactive dancers in time loss duration due to injury (p=.21). CONCLUSION: The only fitness component significantly better in dancers who choose active rest breaks was trunk muscular endurance. This could be attributed to the preferred activities reported by dancers. Although there was no significant difference in other tests, there was a trend of better results in the active group. The potential of implementing rest break activities aimed to improve particular fitness components should be further explored, keeping in mind the overall daily workload (Kozai et al., 2020).